The impact of life satisfaction in the treatment of gaming disorder and other internet use disorders: results from a randomized controlled trial - Müller, Kai W.; Dreier, Michael; Beutel, Manfred E.; Ruckes, Christian; Batra, Anil; Mann, Karl; Musalek, Michael; Wölfling, Klaus (Journal of behavioral addictions, 2023)
According to ICD-11 gaming disorder is currently defined as a behavioral addiction. While our understanding of crucial aspects of this new condition including other subtypes of internet use disorders is growing, less is known about treatment strategies and their effectiveness. Particularly, dimensions of life satisfaction and their meaning for internet use disorders are poorly investigated. The aim of this study was addressing the role of life satisfaction dimensions in a randomized controlled trial. We examined life satisfaction as an additional treatment outcome and investigated in how far life satisfaction is predictive for symptom reduction and related to personality traits.